2022
DOI: 10.1161/jaha.122.026301
|View full text |Cite
|
Sign up to set email alerts
|

Lowering Uric Acid May Improve Prognosis in Patients With Hyperuricemia and Heart Failure With Preserved Ejection Fraction

Abstract: Background An association between uric acid (UA) and cardiovascular diseases, including heart failure (HF), has been reported. However, whether UA is a causal risk factor for HF is controversial. In particular, the prognostic value of lowering UA in patients with HF with preserved ejection fraction (HFpEF) is unclear. Methods and Results We enrolled patients with HFpEF from the PURSUIT‐HFpEF (Prospective Multicenter Observational Study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
(62 reference statements)
0
13
0
3
Order By: Relevance
“…Multiple studies in HFrEF have shown that UA-lowering treatment with benzbromarone or allopurinol failed to improve clinical outcomes, exercise capacity, quality of life, and left ventricular systolic function ( 47 , 48 ). Research in patients with hyperuricemia and HFpEF showed that UA was a predictor for the composite of all-cause mortality and HF rehospitalization and that lowering UA may improve prognosis ( 49 ). This suggests that UA-lowering therapy might help improve the prognosis of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies in HFrEF have shown that UA-lowering treatment with benzbromarone or allopurinol failed to improve clinical outcomes, exercise capacity, quality of life, and left ventricular systolic function ( 47 , 48 ). Research in patients with hyperuricemia and HFpEF showed that UA was a predictor for the composite of all-cause mortality and HF rehospitalization and that lowering UA may improve prognosis ( 49 ). This suggests that UA-lowering therapy might help improve the prognosis of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that NLR was independently associated with the HFpEF, consistent to the report that NLR might be useful to stratify the risk of patients hospitalized with HFpEF 37 . Moreover, previous studies have revealed elevated UA could lead to in ammation and oxidative stress in vascular endothelial cells 19 , and UA was an independent predictor of adverse outcomes in patients with HFpEF [18][19][20]38 . Lowering UA might have a bene cial effect on the prognosis of patients with hyperuricemia and HFpEF 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies have revealed elevated UA could lead to in ammation and oxidative stress in vascular endothelial cells 19 , and UA was an independent predictor of adverse outcomes in patients with HFpEF [18][19][20]38 . Lowering UA might have a bene cial effect on the prognosis of patients with hyperuricemia and HFpEF 19 . In this study, we found the elevation of UA was a diagnostic predictor for HFpEF, suggesting that UA may be a relevant target for clinical prevention and treatment in HFpEF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperuricemia mainly occur in higher primates, including in humans, because the gene encoding urate oxidase is inactivated in higher primates [ 2 ]. Elevated serum uric acid has been found to be associated with adverse outcomes in heart failure patients [ 3 ]. The most common lifestyle risk factor for hyperuricosuria is dietary imbalance, especially consumption of high amounts of fructose, purine meats and beer [ 4 ].…”
Section: Introductionmentioning
confidence: 99%